Molecular Docking, Dynamics Simulation, and Scanning Electron Microscopy (SEM) Examination of Clinically Isolated Mycobacterium tuberculosis by Ursolic Acid: A Pentacyclic Triterpenes - Dian Ayu Eka Pitaloka; Sophi Damayanti; Aluicia Anita Artarini; Elin Yulinah Sukandar (Universitas Gadjah Mada, 2019)
The purpose of this study was to analyze the inhibitory action of ursolic acid (UA) as an antitubercular agent by computational docking studies and molecular dynamics simulations. The effect of UA on the cell wall of Mycobacterium tuberculosis (MTB) was evaluated by using Scanning Electron Microscopy (SEM). UA was used as a ligand for molecular interaction and investigate its binding activities to a group of proteins involved in the growth of MTB and the biosynthesis of the cell wall. Computational docking analysis was performed by using autodock 4.2.6 based on scoring functions. UA binding was confirmed by 30 ns molecular dynamics simulation using gromacs 5.1.1. H37Rv sensitive strain and isoniazid-resistant strain were used in the SEM study. UA showed to have the optimum binding affinity to inhA (Two-trans-enoyl-ACP reductase enzyme involved in elongation of fatty acid) with the binding energy of -9.2 kcal/mol. The dynamic simulation showed that the UA-inhA complex relatively stable and found to establish hydrogen bond with Thr196 and Ile194. SEM analysis confirms that UA treatment in both sensitive strain and resistant strain affected the morphology cell wall of MTB. This result indicated that UA could be one of the potential ligands for the development of new antituberculosis drugs.